1995
DOI: 10.1111/j.1432-1033.1995.tb20628.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Black Widow Spider Neurotoxins Synthesised in Insect Cells

Abstract: alpha-latrotoxin, alpha-latroinsectotoxin and the low-molecular-mass protein from black widow spider venom were synthesised in insect cells using the baculovirus expression system. SDS/PAGE analysis of recombinant-virus-infected cells revealed novel proteins that migrated with sizes similar to those of the neurotoxins from spider venom. The identities of these proteins as alpha-latrotoxin, alpha-latroinsectotoxin or the low-molecular-mass protein were confirmed by immunoblot analysis of infected cells with ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Although their general role in stimulating neurotransmitter secretion is also similar, experimental evidence suggests the latrotoxins vary in target specificity. For example, α-latroinsectotoxin and δ-latroinsectotoxin appear to selectively affect insect neurons, whereas α-latrocrustotoxin stimulates secretion from crustacean neurons, but not from certain insects (Fritz et al 1980; Krasnopernov et al 1991; Magazanik et al 1992; Kiyatkin et al 1995; Elrick and Charlton 1999). The fourth paralog, α-latrotoxin, is a vertebrate-specific neurotoxin that causes the extreme pain following black widow bites (Knipper et al 1986; Kiyatkin et al 1990; Volynski, Nosyreva, et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although their general role in stimulating neurotransmitter secretion is also similar, experimental evidence suggests the latrotoxins vary in target specificity. For example, α-latroinsectotoxin and δ-latroinsectotoxin appear to selectively affect insect neurons, whereas α-latrocrustotoxin stimulates secretion from crustacean neurons, but not from certain insects (Fritz et al 1980; Krasnopernov et al 1991; Magazanik et al 1992; Kiyatkin et al 1995; Elrick and Charlton 1999). The fourth paralog, α-latrotoxin, is a vertebrate-specific neurotoxin that causes the extreme pain following black widow bites (Knipper et al 1986; Kiyatkin et al 1990; Volynski, Nosyreva, et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…The proteins are polypeptides of more than 1300 amino acids and share 34% amino acid identity. Although ␣-LTX and ␣-LIT have been expressed in a recombinant baculovirus expression system (11), it is not clear whether the full-length proteins are toxic. Also, when ␣-LTX was purified from BWSV, it was tightly associated with an acidic low molecular weight protein (12,13).…”
mentioning
confidence: 99%
“…The two helices have quite different characters. The first, PLLILGS (3)(4)(5)(6)(7)(8)(9), is apolar, whereas the second, IQ-AIHDAQR (17)(18)(19)(20)(21)(22)(23)(24)(25), contains polar and charged amino acids. This will result in different interactions with cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…It seems likely that when not exported, this peptide is either destroyed inside the cell or is toxic for the cells. Sequence analysis suggested that the part LPLLILGSLLMTPPVIQA (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), which looks like a transmembrane segment is similar to signal peptides of a variety of proteins [34]. If without an authentic signal peptide this fragment is seen by the expressing cell as a signal peptide, it could be degraded by the appropriate enzymatic system such as one that cleaves the signal peptide of preprolactine within its hydrophobic core, between two leucine clusters [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation